Semi-Markov decision process based congestion control algorithm for video transmission - Bo TIAN; Yi-min YANG; Shu-ting CAI (Tongxin xuebao)
Due to the problem that the congestion control algorithm of transmission control protocol (TCP) cannot meet the requirements of quality of experience for Internet video transmission, a semi-Markov decision process based conges-tion control algorithm for video transmission was proposed. First, in order to improve the accuracy of video quality as-sessment, an online operation no-reference video quality assessment was presented. Then, the congestion control problem was formulated as a semi-Markov decision process according to the feedback of video quality assessment, and the opti-mal parameters of congestion control were obtained by solving the semi-Markov decision process. Simulation results re-veal that proposed algorithm achieves better subjective and objective video quality, and obtains well TCP-friendliness ra-tio, compared with the conventional congestion control algorithms.